Sustainable rubber production through low frequency tapping (d6 and d10) in clone RRII 105 - Karunaichamy K; Rajagopal R; Thomas K U (International Workshop on Latex Harvesting Technology: Sustainable Rubber Production through Good Application Practices of Latex Harvesting Technology, 18-22 November 2013, IRRDB-IRV, Binh Duong, Vietnam.)
Lower frequencies of tapping (d3,d4 and d7) with yield simulation have been successfully extended in many estates and small growers field in India. Two demonstration plots on d6 frequency was intiated during June 2002 at the Central Experiment Station (CES), Chethackal) of Rubber Research Institute of India to study the long term (eleven years) yield response of clone RRII 105. In the first demonstration plot, during 2003-04 dry rubber yield was 4121 kg/400 trees in panel BO-2 (2) and in the second plot dry rubber yield during 2008-09 was 4373 kg/400 trees in panel BO-2(1), which is the highest ever reported yield under weekly tapping. During April 2004,, the d6 plot was shifted to exploratory trial on d10 frequency of tapping with 2.5;ethephon application (16/y). Mean dry rubber yield over eleven years under d6 and d10 frequencies with appropriate stimulation was 2669 kg/400 trees and 2472 kg/400 trees respectively. Total tapping days during the study period for d6 and d10 were 541 and 403 days, respectively.Thus, by adopting d6 and d10 frequencies of tapping, requirement of tapper could be reduced by 65;and 76;respectively. General adoption of LFT is expected to reduce the requirement of skilled tappers in rubber plantation sector.
Keywords: Low frequency tapping; RRII 105; Rubber production